2014
DOI: 10.1021/jp5063379
|View full text |Cite
|
Sign up to set email alerts
|

Shape Effect of Pd-Promoted Ga2O3 Nanocatalysts for Methanol Synthesis by CO2 Hydrogenation

Abstract: In this paper, we present a new approach to investigate metal–support interaction in catalysis. First, we have carried out a controlled growth of two semiconductive Ga2O3 nanocrystals in distinctive shapes, namely, plate and rod with the majority of their surfaces covered with polar and nonpolar facets, respectively. We have then placed the same contents of Pd on these nanocrystals and carried out a systematic testing and characterization for methanol synthesis from CO2 hydrogenation under industrial applicabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 91 publications
0
36
0
Order By: Relevance
“…On the other hand, experimental results indicate that metallic Pd do not show any activity towards the direct conversion of CO 2 into methanol [21,22] . Moreover, as mentioned in the introduction, while many studies report that Pd island supported on metal oxides show good activity toward CO 2 hydrogenation to methanol, it is known that on such system the Pd island only acts as an H 2 dissociation site while the CO 2 /CO hydrogenations occurs on the oxides or Pd-oxides interface [12][13][14][15][16][17][18][19][20] . From these comparisons, it can be inferred that the usage of Pd in the form of small size cluster actually can enhance the catalytic performance of metallic Pd for CO 2 hydrogenation to methanol.…”
Section: Methanol Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, experimental results indicate that metallic Pd do not show any activity towards the direct conversion of CO 2 into methanol [21,22] . Moreover, as mentioned in the introduction, while many studies report that Pd island supported on metal oxides show good activity toward CO 2 hydrogenation to methanol, it is known that on such system the Pd island only acts as an H 2 dissociation site while the CO 2 /CO hydrogenations occurs on the oxides or Pd-oxides interface [12][13][14][15][16][17][18][19][20] . From these comparisons, it can be inferred that the usage of Pd in the form of small size cluster actually can enhance the catalytic performance of metallic Pd for CO 2 hydrogenation to methanol.…”
Section: Methanol Formationmentioning
confidence: 99%
“…Pd island supported on metal oxides (Pd/Oxide) was reported to have good catalytic activities to convert CO 2 directly into methanol [12][13][14][15][16] . In this system, CO 2 adsorption and hydrogenation occurs at the metal-oxide surface [13,17,18] or at the Pd-oxide interface (forming Pd alloy) [18][19][20] . Meanwhile, due to its strong interaction with H 2 molecule, the Pd island only acts as a site for dissociating H 2 molecule and providing the dissociated H atoms to the oxide surface or to the Pd-oxide interface.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of gas-phase heterogeneous hydrogenation of CO 2 to chemicals and fuels, performance optimization usually involves fine tuning the chemical and physical properties of the (photo)catalyst 13 . This can be achieved by doping 4,5 , isomorphous and aliovalent substitution 6,7 , size control 8,9 , morphology changes 10,11 , heterostructuring 1214 , and support and promoter effects 1517 .…”
Section: Introductionmentioning
confidence: 99%
“…The colloidal catalyst was tested in liquidphase methanol synthesis and showed a fourfold increase in activity compared to Cu/ZnO/Al 2 O 3 and Pd/ZnO, comparable methanol selectivity, and high stability at 210°C and 50 bar. Qu et al (2014) prepared Pd supported on plate and rod Ga 2 O 3 nanocrystals. It was observed that Pd supported on plate nanocrystals resulted in higher Pd dispersion and stronger metal-support interaction compared to that of rod nanocrystals supported Pd.…”
Section: Pd-based Catalystsmentioning
confidence: 99%